Eksplorasi Persepsi Penderita tentang Faktor-Faktor Penyebab dan Dampak Penyakit DIabetes Melitus di Wilayah Puskesma Purwokerto Barat, Kecamatan Purwokerto Barat, Kabupaten Banyumas - Sumarwati, Made; Sejati, Waluyo; Pramitasari, Roisca Dyah (Jurnal Keperawatan Soedirman, 2008)
This study explored patient perception about risk factors and impacts of diabetes mellitus. This study used a qualitative descriptive design. Seven participants were interviewed about their perceptions of risk factors and impacts of Diabetes mellitus. The interviews were transcribed and content analysis was used to examine the data. Data analysis revealed the following themes: diet, stress, genetics, and lack of exercise are contributing to Diabetes mellitus. Impacts of the disease are discomfort because of diabetes complication, lack of dependency, sad and cost of treatment. The research outcomes highlight the varied beliefs of participants and numerous impacts of diabetes mellitus.